2008
DOI: 10.1016/j.jmwh.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Demographic, and Risk Behavior Profiles of Pregnant Survivors of Childhood and Adult Abuse

Abstract: Our objective was to address the gap in knowledge about the extent to which perinatal mental health and risk behaviors are associated with childhood and adult experiences of abuse that arises because of barriers to screening and disclosure about past and current abuse. Survey data from an ongoing study of the effects of posttraumatic stress on childbearing were used to describe four groups of nulliparous women: those with no abuse history, adult abuse only, childhood abuse only, and abuse that occurred during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 80 publications
2
53
1
Order By: Relevance
“…The authors brought out another finding: the abuse rates in previous studies were much higher among girls than boys, with a large degree of variability ranging from 6% to 62% for girls and 3% to 16% for boys. Numbers falling within the range of 25% to 33% were found in Seng, Sperlich, and Low's (2008) study as well as more recently (33%) in a review of studies by Strachan (2012). We find the very same rate in a study published by Fairweather and Kinder (2013).…”
Section: Brief Report On a Selection Of Studies Showing High Rates Ofsupporting
confidence: 73%
See 1 more Smart Citation
“…The authors brought out another finding: the abuse rates in previous studies were much higher among girls than boys, with a large degree of variability ranging from 6% to 62% for girls and 3% to 16% for boys. Numbers falling within the range of 25% to 33% were found in Seng, Sperlich, and Low's (2008) study as well as more recently (33%) in a review of studies by Strachan (2012). We find the very same rate in a study published by Fairweather and Kinder (2013).…”
Section: Brief Report On a Selection Of Studies Showing High Rates Ofsupporting
confidence: 73%
“…The vast majority of the research (Beck et al, 2010;Benedict, Paine, Paine, Brandt, & Stallings, 1999;Grimstad & Schei, 1999;Kendall et al, 1993;Leeners, Stiller, Block, Görres, & Rath, 2010;Lev-Wiesel, Daphna-Tekoah, & Hallak, 2009;Linskey & Ferguson, 1997;Polusny & Follette, 1995;Seng, Sperlich, & Low, 2008;Strachan, 2012;Weinstein & Verny, 2004) has been conducted using a retrospective method, with adult women who are asked to recall traumatic memories of their childhood or adolescence. Quite often, these two life stages, although very different, are lumped together in the same category (see Roberts et al, 2004), even though certain qualitative studies (Bonnet, 1999) clearly indicate that children's reactions to sexual aggression depend on their sexual and affective maturity.…”
Section: First Type Of Biasmentioning
confidence: 99%
“…Although there is substantial evidence of childhood physical and sexual abuse as risk factors for PTSD among men and non-pregnant women (1921), few have examined this relationship among pregnant women (2225) and none of the studies included Latin American women. In studies that focused on the antepartum period, only two demonstrated statistically significant associations between childhood sexual abuse and antepartum PTSD; and inferences from these studies are hindered due to incomplete adjustments for potential confounders such as age, race/ethnicity, and comorbid psychiatric disorders including depression (24, 26). In other studies, this association was not significant possibly to lack of adjustment for multivariable confounders, small sample sizes, and variability in assessment of childhood trauma (27, 28).…”
Section: Introductionmentioning
confidence: 99%
“…[66][67][68][69][70][71] Perinatal depression and eating disorder comorbidity Perinatal depression is common in women with an ED history. [10][11][12][13][14][15][16][17] 75 …”
mentioning
confidence: 99%